(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A good work station can support an increase in worker productivity. Increased productivity will have a direct impact on company profits and provide workers with morning comfort. In this research, the role of work station design with reference to standard time, Single-Minutes Exchange of Dies (SMED) and 5S method was carried out. Standard time is used to see how long workers do a job. The SMED method aims to replace an external setup activity with an internal setup that reduces the setup time for an activity. To support the SMED method, it is necessary to design a work station based on the 5S principle. The resulting work system design results in the form of a work station that has considered ergonomic principles to support the performance of workers. The results of the design carried out are expected to increase comfort for workers.